Institute of Technology of Metals of the NAS of Belarus - E. F. Baranovskij; V. M. Iljushenko; Ju. V. Petrunja; V. A. Pumpur (Литьë и металлургия, 2003)
In the article there is described the setting of horizontal continuously stepping casting of zinc bar.